Molecular characterization of metallo β-lactamase producing multidrug resistant Pseudomonas aeruginosa from various clinical samples - Kalaivani Ramakrishnan; Saranathan Rajagopalan; Shashikala Nair; Prashanth Kenchappa; Sheela Devi Chandrakesan (Wolters Kluwer Medknow Publications, 2014)
Introduction: Pseudomonas aeruginosa is a potent opportunistic nosocomial human pathogen among Gram-negative bacteria causing various life-threatening infections in patients from Intensive Care Units. This bacterium has become resistant to almost all commonly available antibiotics with limited treatment options. Multi drug resistant P. aeruginosa (MDRPA) is a major cause of concern among hospital acquired infections. It uses distinctive resistant mechanisms virtually to all the available antibiotics such as Metallo β-lactamases (MBL) production, extended spectrum β-lactamase production (ESBL), up regulation of efflux systems related genes and decreased outer membrane permeability. This study was carried out to find one the predominant resistance mechanisms among MDRPA and the prevalence of corresponding resistance genes. Materials and Methods: MDRPA isolates collected from various clinical samples for a period of 1-year (November 2009-Octo ber 2010) were included to detect the predominant mechanism of resistance using phenotypic and molecular methods. Molecular characterization of all these isolates was done by polymerase chain reaction (PCR) for the presence of blaVIM-2, blaIMP-1, blaOXA-23, and blaNDM-1 genes with specific primers. Results: Among 75 MDRPA isolates 84% (63) were MBL producers. Molecular characterization studied by PCR showed the presence of blaVIM-2 gene in 13% of MBL producers. Conclusion: The prevalence of MBLs has been increasing worldwide, particularly among P. aeruginosa, leading to severe limitations in the therapeutic options for the management. Thus, proper resistance screening measures and appropriate antibiotic policy can be strictly adopted by all the healthcare facility providers to overcome these superbugs.